TeV detection and insights into the emission regions of two gamma-ray fast flaring blazars - Cerasole, Davide; Di Venere, Leonardo; Giordano, Fransesco; Lindfors Elina; Loporchio S.; Pavletic Lovro; MAGIC and Fermi-LAT Collaborations (United Kingdom, 2026)
The γ-ray blazars B2 1811+31 and GB6 J1058+2817 exhibited strong flaring activity in 2020 and 2021, respectively. These high states were observed by the Large Area Telescope on board the Fermi Gamma-ray Space Telescope in the high-energy (HE; 100 MeV < E < 100 GeV) γ-ray band, triggering observations in the very-high-energy (VHE, E > 100 GeV) γ-ray band with the MAGIC telescopes, in UV and X rays with the Neil Gehrels Swift Observatory and in the radio and optical bands with many ground-based telescopes. MAGIC telescopes observations led to the first detection at VHE of both sources. In this contribution, we present the details of these detections and the results of an extensive study of the high-state properties of the two blazars. Fermi-LAT data were used to derive long-term γ-ray light-curves and identify the periods of enhanced activity in both sources. We investigated their spectral properties and temporal variability, with focus on how the strong spectral hardening and the variability timescale can provide information on the γ-ray emitting regions during the flare.
13th Cosmic-Ray International Studies and Multi-messenger Astroparticle Conference 17/06/2024 - 21/06/2024 Trapani, Italy